2016
DOI: 10.1287/mksc.2015.0917
|View full text |Cite
|
Sign up to set email alerts
|

Will a Fat Tax Work?

Abstract: Of the many proposals to reverse the obesity epidemic, the most contentious is the use of price-based interventions such as the fat tax. Previous investigations of the efficacy of such initiatives in altering consumption behavior yielded contradictory findings. In this article, we use six years of point-of-sale scanner data for milk from a sample of over 1,700 supermarkets across the United States to investigate the potential of small price incentives for inducing substitution of healthier alternatives. We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…Details of the design and findings of the studies included in the review are presented in Table . Thirty studies (79%) reported the percent change in consumption of the target food or nutrient, or the percentage of total calories, and also presented the tax (or hypothetical tax) as a percentage of price.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the design and findings of the studies included in the review are presented in Table . Thirty studies (79%) reported the percent change in consumption of the target food or nutrient, or the percentage of total calories, and also presented the tax (or hypothetical tax) as a percentage of price.…”
Section: Resultsmentioning
confidence: 99%
“… 8,19,20,21,26,40,46,42,24,18,43,23 C : Taxes on individual nutrients (fat, salt, sugar). D : Taxes based on nutrient profiling. 16,17,43,44,49,50,53,55 *Nonsignificant.…”
Section: Resultsmentioning
confidence: 99%
“…Khan et al (2016) andGriffith et al (2018) apply a similar approach to analyze the impact of a tax on fat content.5 Another set of papers study soda taxes outside of the US. Grogger (2017),Aguilar et al (2016), andColchero et al (2017) investigate the effects of SSB taxes in Mexico Berardi et al (2016).…”
mentioning
confidence: 99%
“…Khan et al (2016)'s analysis of the "fat tax" is an example of a timely assessment of a contemporaneously relevant policy question relevant to consumers and marketing. A Frontiers version of these papers would of course have a shorter, briefer "to the main contribution point" introduction and literature review with much of the validation and robustness analysis in a supplemental online appendix.…”
Section: Exemplarsmentioning
confidence: 99%